International Financial Transactions and Exchange Rates : Trade, Investment, and Parities - Kallianiotis, John N.; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2013)
The book describes the roles of theories, systems, and exchange rates, and gives practical solutions for multinational business, individuals, and nations.
Keywords: Science; Science; Science, general